THE USE OF LEARNING MEDIA THROUGH E-MODULES IN THE M. CARCASSI GUITAR COURSE AT THE MUSIC EDUCATION STUDY PROGRAM, STATE UNIVERSITY OF JAKARTA - Aristanisa, Vania (Synergy : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to develop and use the Learning Media E-Module of Matteo Carcassi Guitar Course at the Music Education Study Program, State University of Jakarta. This research is a type of Action Research research that is collaborated with development research. In the media development process, researchers use the ASSURE development model developed by Smaldino. The ASSURE development model consists of 6 stages, namely 1) Analyze characteristic learner, 2) State Objective, 3) Select Methode, Media and Materials, 4) Utilize Media and Materials, 5) Requires Learner Participation, 6) Evaluate and Revize. The data collection techniques used are interviews, observations, and questionnaires. Quantitative and qualitative data were analyzed using the Likert scale. Based on the conclusions of the research data, researchers obtained the following results: 1) The results of the analysis of student characteristics showed that 78.21% of the 21 students of the Music Education Study Program class of 2022, State University of Jakarta have an audio-visual learning style, so it is necessary to develop audiovisual-based media, namely E-Modules. 2) From the analysis of student needs, it shows that 90.5% of 21 students agree and are interested in developing E-Module-based learning media. 3) The e-module media that has been developed has passed validation by 2 experts including learning media experts and learning material experts. Based on validation that has been carried out by learning media experts, it resulted in a score of 98.4% so that it reached the "Excellent" category. While the validation that has been carried out by material experts has resulted in a score of 97.6%, which is classified as the "Excellent" category. 4) From the results of the evaluation through media field trials to students showed good enthusiasm, from the student response test produced a score of 92.29% by reaching the "Very positive" category. Therefore, the e-module-based learning media product that has been developed by researchers is very suitable and feasible to use in the learning process of Matteo Carcassi Guitar. After the development process is complete, E-modules are also used in the learning process in the classroom and have an influence in the form of changes in grades after using media with an average student score of 74.9 so that E-module media can be categorized as media that are effectively used in class